Comparison of Effects of Morning versus Evening dosing of Anti-hypertensive Medications on Blood Pressure Control and Complications - Saleem, Maryam; Fakhr, Amer; Amer, Ahsan; Amer, Ahmed (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare blood pressure control in morning versus evening dosing of anti-hypertensive medications in hypertensive patients. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Medicine, Pak-Emirates Military Hospital Rawalpindi, Pakistan from Jan to Aug 2023. Methodology: Total 450 hypertensive patients were enrolled and segregated into two groups of 225 each. Group-A was given anti-hypertensive in the morning while Group-B was given in the evening. Blood pressure was noted at the start of the study and on every 2 monthly follow-ups with medication titration. Variables including hypertension duration, medications and complications were assessed and compared. Results: A total 268 patients were included in the final analysis with a mean age of 48.03±9.70 years in Group-A and 48.38±10.02 years in Group-B participants. Non-fatal myocardial infarction was in 51(36.2%) of Group-A and 43(33.9%) of Group-B individuals. Baseline systolic and diastolic BP were 154.24±12.03 & 91.96±5.56 mmHg respectively in morning dosing group and 156.58±12.36 & 92.77±6.13 mmHg in evening dosing group. There was slightly better control in the evening dosing group with SBP and DBP at the 6-month follow-up 141.40±4.22 and 85.28±3.05 mmHg respectively versus 142.23±5.26 and 86.60±3.58 mmHg in morning dosing group. Conclusion: Slightly well but statistically insignificant control of SBP and DBP was observed in the evening dosing group with no significant difference in overall BP control and complications.